Promoting Natural Hazards Triggering Technological Disasters (NATECH) in Malaysia - Bin Mohd Zain, Mohd Zainoor Annuar (International Journal of Humanities and Education Development (IJHED), 2022)
Malaysia is a fast-growing country in Southeast Asia that is experiencing rapid technological development. This increases the risk of technological disasters and occupational hazards that can be triggered by natural hazards. This paper stresses the linkage of natural hazards with technological disasters, or NATECH, that remains a rather new term within the Malaysian context. Given the lack of current information on NATECH risk nationwide, this article intends to provide Malaysia-specific cases. This paper report on some significant local NATECH cases that have not been given any public access and not published in scholarly journal. I also highlight that communication and valuable information-sharing are crucial to an effective and efficient disaster management framework. There is still gaps and missing barriers in the nation’s readiness and resilience towards NATECH disasters. In Malaysia, the information regarding NATECH risks has hardly been shared outside of the industrial fence, resulting in low level of awareness on the lessons and knowledge for better future proofing.